STRUKTUR PENULISAN NASKAH PADA SIARAN RADIO - Winda Kustiawan; Tasya Salsabila (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
Radio news scripts are news scripts that are ready to be delivered or read by the broadcaster. The definition or understanding of the script itself is a story that is described in sequence from scene to scene which is equipped with a place or setting, circumstances, dialogue, and often there are characterizations in it. 94% in writing this article using the method of reading and searching for internet sources. In this study, the method used is descriptive qualitative method. News script writing plays a very important position in radio news broadcasts. In writing broadcast scripts, scriptwriters must be able to write in a conversational or spoken language style in a concise, concise, and clear manner. Broadcast Script is broadcast material that will be delivered by broadcasters in broadcasting, especially broadcasts with script reading techniques.